Objective measurement of mushroom quality relative to industry inspectors. (12th December 2006) - Kusabs, N.J.; Trigg, L.; Bollen, A.F.; Holmes, G.
A machine learning classification system has been developed to sort mushrooms into similar quality grades to those used by human inspectors. The attributes considered for the algorithm included weight, firmness, image features and some subjective scales of the common cultivated button mushroom. Two grading systems were tested; one involving three broad quality grades and a more detailed five-grade system. Two machine learning methods were used to build quality prediction models, relative to the mushroom quality grade criteria specified by the inspectors. A head inspector was used as a reference grading expert and the mis-classification error of the models based on his/her grading for both three and five grades varied from 17 to 22%. The accuracy of the quality prediction models is at the upper level of the variation measured between mushroom industry inspectors. This machine learning classification system provided insights into the subjective decision-making regarding mushroom quality.